Financial Ratio Analysis As An Instrument For Evaluating The Financial Performance Of The Padang City Drinking Air Resources In Optimizing Fund Management - Umniati Khairunnisa; Nur Aliah; Dwi Saraswati (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to evaluate the financial performance of Perumda Air Minum Kota Padang through financial ratio analysis as an instrument to optimize the company's fund management. Using a descriptive quantitative approach, this research analyzes financial report data from 2022 to 2024, focusing on liquidity, solvency, profitability, activity, and operational ratios based on the standards of the Minister of Home Affairs Decree Number 47 of 1999. The results indicate that the company's financial performance falls into the "Good" category, with key strengths in low-risk solvency and high receivables collection effectiveness, but weaknesses in suboptimal profitability and operational efficiency influenced by high costs and water loss levels. The value of this research lies in providing strategic recommendations to enhance cost control, accelerate collection, and reduce water loss, thereby supporting operational sustainability and public services. Financial ratio analysis proves effective as an evaluation tool that aids management in decision-making for fund optimization.